Sustainability through Art - Lopes, Ana Cruz (2017)
One of the most prominent urban problems European cities face, is not only the physical degradation of its historic city centers, but also the degradation of their social, economic and environmental context. Moreover, common rehabilitation methods and strategies are often unsuccessful combatting such problem, and new ways and strategies must be researched, tested, and implemented under a new sustainable development policy. Creativity and artistic activities can play an important role in the resolution of this problem. For example, the re-occupation of derelict buildings, through creative and innovative activities, can contribute to resolving the primary issue. While analyzing a comparative case study using three examples: LxFactory in Lisbon, Ateneu Popular 9 Barris in Barcelona, and 59 Rivoli in Paris, its possible to conclude that their rehabilitation through art and culture, could produce positive side effects leading to social renovation and solid economic activity within itself and its surrounding area, creating new local economies, jobs, new tourists attractions, real estate opportunities and more. Considering the current standpoint and outlook on rehabilitation, as an action and movement of sustainability, especially at the environmental level, and associating it with the arts and culture movement, will allow it to solve the social and economic problem simultaneously. By introducing new dynamic living spaces in unoccupied and derelict buildings also re-energizes the economic value of the building as well as, most importantly, regenerating the actual city.